Examining gender difference in disordered eating behaviour and its associated factors among college and university students in Sarawak - Cheah, Whye Lian; Edmund Chin, Vui Shin; Helmy, Hazmi (SAGE Publications Inc., 2022)
Background: Disordered eating is common among late adolescents and young adults who pursue an idealised body image. Aims: This study aims to determine the prevalence of disordered eating between males and females and its associated factors among college and university students in Sarawak. Methods: A cross-sectional study involving 20 public and private colleges and universities in Sarawak, from September 2017 to March 2020. Respondents completed self-administered questionnaires both in the English and Malay language. Data about sociodemographic characteristics, body mass index, eating attitude, body dissatisfaction, perceived sociocultural pressure, self-esteem, drive for muscularity and perfectionism were collected. Results: A total of 776 respondents (male: 30.9%; female: 69.1%) aged 19 to 25 years old took part in the study. The overall prevalence of disordered eating was 25.2% (95% confidence interval (CI) 21.9; 28.7) with females (28.6%, 95% CI 24.6; 32.9) higher than males (15.6%, 95% CI 10.5; 21.9). Multivariate analysis showed for both male and female models, perceived sociocultural pressure (male: β=1.125, p < 0.01; female: β=1.052, p=0.003), drive for muscularity (male: β=1.033, p=0.017; female: β=1.032, p < 0.01) and perfectionism (male: β=1.098, p=0.02; female:β=1.119, p < 0.01) were predictors for disordered eating. Conclusion: The prevalence of disordered eating among college and university students in Sarawak was high. The findings suggest that although there were gender differences in the prevalence of disordered eating, its associated factors were the same. The findings of this study will be useful for designing and implementing disordered eating prevention and intervention programme.